Status of Differently-Abled Persons in Work Place: A Study of Courts inside Kathmandu Valley - Aryal, Anupa (Kathmandu School of Law Review, 2017)
Nepal has been adopting a range of policy, legal and institutional measures for the protection and promotion of the rights of persons with disabilities even before the CRPD came into force. It enacted the Disabled Protection and Welfare Act (DPWAct) in 1982 and the Disabled Protection and Welfare Regulation in 1994. These acts intend to protect and promote the rightsand interests of the persons with disabilities, recognize the need for the preventionof disability, and provide welfare services such as health, education, care and training to the persons with disabilities in order to make them competent and capable enough. This paper after empirical research using interview and observation method as data collection tool, tries to identify whether the rights to persons with disability are properly protected and promoted in Nepal.